Consumer Fraud Mode by Tricking Prices through Hyperbolic and Persuasive Advertising Promotion Language - Pratikno, Heru; Suseno, Imam; Saifullah, Aceng Ruhendi (Universitas Tidar, 2024)
In trading activities, sometimes certain people take advantage of the situation to take as much profit as possible from consumers. What these parties do is sometimes done in deceptive ways. However, strangely, consumers are actually tempted by their products, and do not even mind their deception. This has the potential to become a legal problem because of the attempt to deceive consumers with ironic slogans and promotional language. Therefore, the purpose of this research is that the author wants to know how sales cases that occur in minimarkets and online shops have the potential to become legal problems. In addition, the author wants to know what kind of promotional language minimarkets and online shops use to manipulate the selling price so that it looks cheaper to consumers so that it has the potential to become fraud. The data collection used in this research uses observation and documentation methods. After that, the data that has been collected will be analyzed using a qualitative approach. The results show that the use of advertising promotional language can increase sales value. On the other hand, the language has the potential to become a legal case because there are elements of price fraud against consumers in accordance with Article 378 of the Criminal Code.